2021
DOI: 10.3390/pharmaceutics13071076
|View full text |Cite
|
Sign up to set email alerts
|

Two in One: Use of Divalent Manganese Ions as Both Cross-Linking and MRI Contrast Agent for Intrathecal Injection of Hydrogel-Embedded Stem Cells

Abstract: Cell therapy is a promising tool for treating central nervous system (CNS) disorders; though, the translational efforts are plagued by ineffective delivery methods. Due to the large contact surface with CNS and relatively easy access, the intrathecal route of administration is attractive in extensive or global diseases such as stroke or amyotrophic lateral sclerosis (ALS). However, the precision and efficacy of this approach are still a challenge. Hydrogels were introduced to minimize cell sedimentation and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The developed AHM showed improved cell viability and a lack of immune response. The Mn 2+ -labeled AHM produced a strong T1 MRI signal [ 87 ]. The AHM also showed its potential in neuro-regenerative applications.…”
Section: Tissue Engineering With Ahmsmentioning
confidence: 99%
“…The developed AHM showed improved cell viability and a lack of immune response. The Mn 2+ -labeled AHM produced a strong T1 MRI signal [ 87 ]. The AHM also showed its potential in neuro-regenerative applications.…”
Section: Tissue Engineering With Ahmsmentioning
confidence: 99%
“…HA) [30,31] or contrast agents (e.g. manganese ions for alginate) [32] will help guide further development of space conforming [32] and biodegradation [30] as well as the precision of injection into the stroke cavity. Most preclinical stroke studies use healthy young male adult rodents whereas human stroke is usually complicated by age and multi-morbidities in both sexes [33] in which host tissue-hydrogel interactions are underexplored (Table 1).…”
Section: Regenerative Hydrogels: a "Second-generation" Therapeutic Ap...mentioning
confidence: 99%
“…Coupled with their absorptive capacity [87], these properties make alginate-based hydrogels very effective as wound dressings, with the ability to absorb wound exudate and promote tissue repair [89]. In addition to being non-toxic [32,87], alginate-based hydrogels do not elicit an inflammatory response in vivo [32] and their easy administration make alginate-based hydrogels a promising and effective payload delivery vehicle for pharmacological compounds and regenerative stem cells [90]. Chitosan in generated by the deacetylation of chitin, a natural polysaccharide obtained from the exoskeletons of crustaceans, insects and fungi [91].…”
Section: Text Box 5: Basic and Historical Details Of Alginate Hydrogelsmentioning
confidence: 99%
“…149 Because hydrogels can be labeled and imaged relatively quickly, they offer seamless precision for procedures. 150 RNA viruses capitalize on the ability of nucleoproteins to package mRNA. It has been shown that, under some circumstances, transmembrane proteins can interact and package other mRNA-bearing RNA-packaging signals in the form of virus-like particles.…”
Section: Mrna-based Cell Engineeringmentioning
confidence: 99%